Class I HDAC inhibition improves object recognition memory consolidation through BDNF/TrkB pathway in a time-dependent manner. (1st April 2021) - Ramirez-Mejia, Gerardo; Gil-Lievana, Elvi; Urrego-Morales, Oscar; Soto-Reyes, Ernesto; Bermúdez-Rattoni, Federico
Abstract: There is increasing evidence showing that HDACs regulates BDNF (brain-derived neurotrophic factor) expression through its interaction with the Bdnf gene promoter, a key regulator to consolidate memory. Although the nuclear mechanisms regulated by HDACs that control BDNF expression have been partially described recently, the temporal events for memory consolidation remain unknown. Hence, in this work, we studied the temporal pattern for the activation of the BDNF/TrkB pathway through class I HDAC inhibition to enhance object recognition memory (ORM) consolidation. To this end, we inhibited class I HDAC into the insular cortex (IC) and a weak ORM protocol was used to assess temporal expression and function of the BDNF/TrkB pathway in the IC. We found that cortical class I HDAC inhibition enhanced long-term ORM, coincident with a clear peak of BDNF expression at 4 h after acquisition. Furthermore, the tyrosine kinase B (TrkB) receptor blockade at 4 h, but not at 8 h, impaired the consolidation of ORM. These results suggest that histone acetylation regulates the temporal expression of BDNF in cortical circuits potentiating the long-term recognition memory. Highlights: Cortical class I HDAC inhibition facilitates long-term ORM consolidation. Cortical class I HDAC inhibition temporally enhances BDNF after weak ORM training. Blockade of TrkB receptor at 4 h impairs weak ORM consolidation.